1977
DOI: 10.1111/j.1399-3054.1977.tb04034.x
|View full text |Cite
|
Sign up to set email alerts
|

NADH and NADPH Dependent Malate Dehydrogenases of Phaseolus vulgaris

Abstract: French bean (Phaseolus vulgaris L. cv. Contender) leaf extracts catalyse the reduction of oxaloacetate to malate in the presence of NADH and NADPH. Under the experimental conditions used, the optimum pH values are 8 and 6 respectively. After chromatography on diethylaminoethyl cellulose, two principal forms of NADH‐MDH (L‐malate: NAD+ oxidoreductase, E.C. 1.1.1.37) upon which NADPH activities are superposed, can be characterized. This result is confirmed by electrophoresis on polyacrylamide gel. On the other h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

1979
1979
1994
1994

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 16 publications
3
6
0
Order By: Relevance
“…The second optimum at pH 8.0 was associated with a chloroplastic enzyme which required DTT for activation. Similar results were obtained for NADP-malate dehydrogenase extracted from leaves of Phaseolus vulgaris (22). These authors showed that the activity at the lower pH was due to an NAD-malate dehydrogenase which also exhibited NADP-dependent activity.…”
Section: Methodssupporting
confidence: 80%
“…The second optimum at pH 8.0 was associated with a chloroplastic enzyme which required DTT for activation. Similar results were obtained for NADP-malate dehydrogenase extracted from leaves of Phaseolus vulgaris (22). These authors showed that the activity at the lower pH was due to an NAD-malate dehydrogenase which also exhibited NADP-dependent activity.…”
Section: Methodssupporting
confidence: 80%
“…The relatively high activity of the NADP-MDH of guard cells in the dark can be ascribed to an incomplete specificity of the NAD-MDH, as has been reported for leaf and root extracts of P. vulgaris (28), and confirmed by us with pea leaf extracts and extracts of pea leaf guard cells. It was possible to separate a DTT-dependent activity from that detected without preincubation with DTT, the latter comigrated with the NADdependent activities (Fig.…”
Section: Amounts Of Nadp-mdh In Extracts Of Guard Cells and Mesophyllsupporting
confidence: 81%
“…However, the ratio between the DTT-independent and the DTT-stimulated NADP-MDH activities was lower than in guard cell extract. Vidal et al (28) had obtained an MDHactivity profile comparable to that shown in Fig. 3A, when they separated a leaf extract of P. vulgaris on a DEAEcellulose column.…”
Section: Separation Of Mdh Activities In Epidermal Extractsmentioning
confidence: 59%
See 1 more Smart Citation
“…Activity of MDH was estimated according to the method of Vidal et al (1977). The assay mixture contained lOmM oxaloacetate and 5 mM EDTA in 50 mM Tris-HCl buffer, pH 7'6.…”
Section: Enzyme Assaysmentioning
confidence: 99%